Marine sublittoral benthos fails to track temperature in response to climate change in a biogeographical transition zone. (23rd August 2018) - Gaudin, François; Desroy, Nicolas; Dubois, Stanislas F; Broudin, Caroline; Cabioch, Louis; Fournier, Jérôme; Gentil, Franck; Grall, Jacques; Houbin, Céline; Le Mao, Patrick; Thiébaut, Éric
Abstract: Species ranges are shifting globally to track temperature changes in response to climate warming, with substantial variability among taxa. In the English Channel, a biogeographical transition zone between the cold temperate and warm temperate provinces of the North-East Atlantic, distribution shifts have been relatively well documented for plankton, fish and intertidal benthic organisms, but little information is available on sublittoral benthos. Following a description of the magnitude of the sea bottom temperature (SBT) rise, the changes in the distribution and occupancy of 65 benthic invertebrate species were analysed by comparing data collected throughout the English Channel at more than 200 stations sampled during a cool period in the 1960s–1970s and at present in 2012–2014. A non-uniform rise in SBT for the last three decades was observed at the regional scale, varying from 0.07 to 0.54°C per decade. This rise differs from that reported for sea surface temperature (SST) in stratified areas suggesting that SBT should be used rather than SST to analyse responses of subtidal organisms to climate change. Despite shifts in both minimum and maximum sea bottom isotherms (2.5 and 3.2 km.year −1, respectively), the distribution centroid shift of most species remained <1.0 km.year −1, regardless of the average temperatures they usually experience. Conversely, decreases were observed in the occurrence of most cold-water species and increases were found in the occurrence of most warm-water species. These results suggest that ongoing climate change could lead to a decrease in benthic biodiversity at range limits, especially where connection routes are lacking for new migrants.